POPULATION DYNAMIC OF Viscum articulatum Burm. f. ON ITS HOST IN PURWODADI BOTANIC GARDEN - Solikin Solikin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
V. articulatum Burm. f. is a parasitic plant that has potential as medicinal plant. The research aim is to study the population dynamic and hosts of V. articulatum Burm. f. in Purwodadi Botanic Garden which was conducted in April-September 2013 by cruising method and literature study on previous research of parasitic plants in Purwodadi Botanic Garden. The results show that V. articulatum Burm. f. found living as hyperparasite on the parasite Dendrophthoe pentandra (L.) Miq. The population number of V. articulatum Burm. f. increased following the increasing of host and time. The species, genera and family of the host trees increased from 20 species, 14 genera and 13 families in 2005 to 23 species, 19 genera and 17 families in 2013.